2003
DOI: 10.1210/jc.2002-021299
|View full text |Cite
|
Sign up to set email alerts
|

Expression Profile of the Telomeric Complex Discriminates between Benign and Malignant Pheochromocytoma

Abstract: Telomerase, a ribonucleoprotein complex that includes the telomerase RNA component, the telomerase-associated protein (TP1), the telomerase catalytic subunit (hTERT), and the heat shock protein 90 (HSP90), is closely related to the malignant potential of human tumors. In pheochromocytomas (PC) it is very difficult to predict malignant potential by conventional histology or immunohistochemical and molecular markers. To test whether the expression of telomerase subunits is reflected in the malignant transition o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
51
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(53 citation statements)
references
References 36 publications
(38 reference statements)
2
51
0
Order By: Relevance
“…Therefore, they have not yet had a significant impact on changes in pathological diagnosis and follow-up management. Previous studies have suggested that the Ki-67 index may be valuable in the diagnosis of malignant PCC (13)(14)(15). The classification using the Ki-67 index alone may be considered as simple and easy to apply in the clinical setting.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, they have not yet had a significant impact on changes in pathological diagnosis and follow-up management. Previous studies have suggested that the Ki-67 index may be valuable in the diagnosis of malignant PCC (13)(14)(15). The classification using the Ki-67 index alone may be considered as simple and easy to apply in the clinical setting.…”
Section: Discussionmentioning
confidence: 99%
“…Underlying genetic mutations and molecular alterations associated with malignancy have led to the identiication of molecular therapeutic targets that include the mammalian rapamycin (mTOR) protein kinase, which is known to be upregulated in malignant pheochromocytomas [65], angiogenesis-mediated growth factors such as vascular endothelial growth factor (VEGF) and heat shock protein 90 (Hsp90), which are also overexpressed in malignant pheochromocytomas [66]. The mTOR inhibitor, Everolimus, has been used in a number of patients with malignant pheochromocytomas, but results have been disappointing [67].…”
Section: Targeted Therapymentioning
confidence: 99%
“…The sum of the scores groups adrenal pheochromocytomas into those with potential for biologically aggressive behavior (PASS) and those likely to behave in a benign fashion (PASS Ͻ4). [117], heat shock protein 90 [118], and telomerase complex proteins [119] have all been studied with varying degrees of success.…”
Section: Histological Scoring Systemsmentioning
confidence: 99%